PENDUGAAN MUKA AIR TANAH MENGGUNAKAN METODE ELEKTROMAGNET - Gautama, Gregorius Aryoko; Novianto, Dandung; Suhardono, Agus (Universitas Islam Balitar Blitar, 2024)
Landslides and moving land occurred in Brau Village, Gunungsari, Batu, East Java in 2022 caused by soil that was saturated with water. The state of water saturation is caused by high rainfall, causing a lot of water trapped below the surface. The Gunungsari One-Roof School and the hill in Brau Village, Gunungsari, Batu, East Java experienced moving soil, causing one of the buildings in the elementary school to be damaged. This study aims to estimate the depth of the groundwater table in the area that landslides. The method used is the electromagnet method which utilizes electromagnets to detect water, soil, and rocks. Interpretation of field data based on type resistance is generally done by analyzing the physical properties of rocks, namely type resistance, porosity, rock permeability, mineral content, water presence, weathering, fracturing, and others. The trajectories in the study were T1, T2, T3, and T4. Track length T1=42m, track T2=44m, track T3=36m and track T4=30m. The distance between the tracks T1-T2=117m, T2-T3=20m, and T3-T4=55 m. The depth of the groundwater table in the T1 track is 90m with a groundwater thickness of 15m. The T2 track is a groundwater table at a depth of 10m with a thickness of 50m and a depth of 90m with a thickness of 210m. The T3 track depth of the groundwater table at 65m with a thickness of 235m. The depth of the groundwater table in the T4 track is 195m with a thickness of 60m. T2 and T3 trajectories, shallow groundwater depth, and very thick groundwater thickness are the causes of landslides. The relocation of Sekolah Satu Atap Gunungsari is one option if you look at the data obtained and the nature of the soil, the research location is immediately relocated, otherwise, when entering the rainy season, the volume of water stored in the soil is getting thicker and the depth of the aquifer is increasing.